The Relationship between the Knowledge of Posyandu Cadres and the Implementation of Stunting Prevention in Community Midwifery Practices - Ulfah Jamil, Maria; Rizki Amalia, Novianti; Mulyana, Asep; Nurakilah, Heni (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2024)
Introduction: Stunting is a child's failure to achieve his growth potential due to serious malnutrition and often experiencing illness in his childhood, thus determining his growth and development abilities and mental and will cause long-term damage. The prevalence of stunting in Indonesia from the results of the Indonesian Nutrition Status Survey (SSGI) decreased from 24.4% in 2021 to 21.6% in 2022, while the World Health Organization (WHO) standard must be below 20%. The problem of stunting is a big problem, because in stunted children, not only their physical growth is disturbed, but it will also affect their brains. In handling stunting, the government involves several parties, one of which is posyandu cadres, but not all posyandu cadres know about stunting prevention. Objective: The purpose of this study is to find out and evaluate the relationship between the knowledge of posyandu cadres and the implementation of stunting prevention in community midwifery practices. Method: The method used in this research is an analytical survey with a cross sectional approach. The sample in this study met the inclusion criteria as many as 21 people. Result: The results of this study show that good posyandu cadres have a high level of knowledge in implementing stunting prevention in community work practices. Conclusion: Based on the research results obtained, there is a relationship between posyandu cadres' knowledge and the implementation of stunting prevention.